(3GdSjQ hGdSdhc Edi edc Gdedhcs - (3bGSe Hf UdGM GdOjf GdNGfj GdMdHj,J (B1109 (3g` s ((3eMeO Hf SGde GdHJfhfi GdWhjd s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CgHW HMceJfg CSQGQ PGJg ef SeGA GdSeG Edi CQV GdWHjYI GdcdjI hHYO aEf Sdhc WQjb GdMb ef CNdGb GdfHjjf hGdeQSdjf hNGUI YHGO Gddg GdUGdMjf s
(3BNQgG (B:s
(3hdG JbOQ CjgG GdCN Ydi QOgG EdG HGdJeSc HGdTQjYI hUMHI GdYdeGA hUdi Gddg Ydi SjOfG eMeO s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B104 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B833s
Keywords: (3GdJUha hGdBOGH GdTQYjIs